SQL Database-Based Child Physical Health Risk Assessment System. (8th July 2022) - Zhu, Junjie; Li, Bo; Li, Junshi; Wang, Zuopeng; Cui, Xinghe
Abstract : The purpose of this study is to investigate the relationship between the various factors that affect children's physical health. By analyzing the physical examination results of 1, 000 children who had health examinations in the hospital from June 2019 to June 2021 in a SQL database, we were able to determine the factors influencing children's physical health. Additionally, a method for assessing the physical health risks being faced by children is developed. To increase the evaluation's effectiveness, a new type of physical health risk assessment system for children is being developed on the basis of the original physical health risk assessment system for children. The system hardware component optimizes the primary control chip and minimizes the system circuit to the smallest possible size. Simultaneously, a model for risk assessment of physical health is developed in children and a risk quantification procedure is implemented. The membership degree of the risk value is calculated using the fundamental concept of fuzzy logic, and the evaluation result is incorporated into this step of the computation to generate an accurate evaluation level. To date, no system for assessing physical health risks in children has been developed. We discovered while building the system test that the query accuracy of this system's evaluation level can reach up to 96%, the detection time is reduced to a minimum of 5 seconds, and the usage effect is improved.